Gaseous Pollutants and Particulate Matter in Ambient Air: First Field Experiment in an Urban Mediterranean Area (Nador, Morocco) - Bouchra Oujidi; Abdelfettah Benchrif; Mounia Tahri; Fatiha Zahry; Moussa Bounakhla; Hocein Bazairi; Nadia Mhammdi; Maria Snoussi (Aerosol and Air Quality Research, 2023)
Abstract Mediterranean urban areas are reportedly affected by poor air quality due to numerous emission sources, as well as topography and meteorological conditions that facilitate the accumulation of pollution. This present study makes an initial attempt to assess the effect of gaseous pollutants (NO2, CO, and O3) and particulate matter (PM2.5 and PM10) on the air quality of Nador city, which lies on the Mediterranean coast of Morocco. Three daily, short-term sampling campaigns were conducted between 2016 and 2018 in an urban area. The concentrations of PM2.5 and PM10 together with elemental compositions (up to 16 elements) and black carbon content were determined. The obtained data were characterized using descriptive analysis, correlation matrices, elemental enrichment factors (EFs), and elemental ratios. On average, the particulate matter and gaseous pollutant concentrations were below the national standard limits. Two categories of PM2.5 and PM10 sources, as derived from the EF investigation, were defined as soil/crustal (Ti, Al, Mn, Sr, K, Na, Ba, and V) and anthropogenic (Ni, Cr, Cu, Zn, and Pb). For black carbon, biomass burning was found to be the largest contributing source (3.1–8.4 µg m−3), more so than fossil fuels (0.9–1.8 µg m−3). This study highlights that an air quality management plan should be established for Nador city, including the implementation of a network of monitoring stations to help with identifying and controlling the activities causing air pollution.